9514 1404 393
Answer:
-12, -21
Step-by-step explanation:
Let x represent the first number. Then the second is x-9. The other relation is ...
4x = 2(x-9) -6
2x = -24 . . . . . subtract 2x, simplify
x = -12
x-9 = -21
The first number is -12; the second number is -21.
Answer:
$20.60
Step-by-step explanation:
$25.75 x 20% = $5.15
$25.75 - $5.15 = $20.60
Answer:
f(x) is shifted to the left 2 units of g(x)
f(x) will not be shifted vertically since we did not add anything to g(x)
Step-by-step explanation:
g(x) = x^2+2
f(x) = g(x+2)
When we shift with h(x+c) it is a horizontal shift
if c>0 it moves it left c units
if c< 0 it moves it right c units
Since c is 2, this is shifted left 2 units
f(x) is shifted to the left 2 units of g(x)
When we shift with h(x)+c it is a vertical shift
if c>0 it moves it up c units
if c< 0 it moves it down c units
f(x) will not be shifted vertically since we did not add anything to g(x)